Tagget - Greenfield, Irving A. (England : Hamlyn Paperbacks, 1979)
Thirty-five years later he can remember only a few terrifying fragments of the secret role he played at the centre of Operation Overlord...and the methods used to help him forget.
Keywords: Fiction